CD4 T Cells Mediate Both Positive and Negative Regulation of the Immune Response to HIV Infection: Complex Role of T Follicular Helper Cells and Regulatory T Cells in Pathogenesis - Phetsouphanh, Chansavath; Xu, Yin; Zaunders, John (Frontiers in Immunology, 2015)
HIV-1 infection results in chronic activation of cells in lymphoid tissue, including T cells, B cells and myeloid lineage cells. The resulting characteristic hyperplasia is an amalgam of proliferating host immune cells in the adaptive response, increased concentrations of innate response mediators due to viral and bacterial products, and homeostatic responses to inflammation. While it is generally thought that CD4 T cells are greatly depleted, in fact, two types of CD4 T cells appear to be increased, namely regulatory T cells (Tregs) and T follicular helper cells (Tfh). These cells have opposing roles, but may both be important in the pathogenic process. Whether Tregs are failing in their role to limit lymphocyte activation is unclear, but there is no doubt now that Tfh are associated with B cell hyperplasia and increased germinal centre activity. Antiretroviral therapy (ART) may reduce the lymphocyte activation, but not completely, and therefore there is a need for interventions that selectively enhance normal CD4 function without exacerbating Tfh, B cell or Treg dysfunction.